Fragmente römischer Grabbauten aus Segobriga und Augusta Emerita - Trunk, Markus (Madrider Mitteilungen, 2020)
This article presents hitherto unknown architectural fragments belonging to Roman funerary monuments from Segobriga and Augusta Emerita. In one case, it originates from recent excavations, in the other case, it is an old finding of the 19th century. Both are entirely exceptional compared to the common forms of tomb-types on the Iberian Peninsula.